IMPLEMENTATION OF PICTURE STORY LEARNING TO IMPROVE ENGLISH LANGUAGE SKILLS IN EARLY CHILDHOOD - Ratna Rosanti, Ika; Nabilla Maghfi, Ulfah (Tahsinia, 2024)
This study aims to explore the application of the picture story learning method in improving English language skills in early childhood. The picture story method is known as an effective tool in facilitating children's language development through a combination of pictures and narratives, which allows children to associate words with meanings visually and contextually. This study involved 30 children aged 4–6 years in a kindergarten, who were divided into two groups: an experimental group that used picture stories in English learning, and a control group that received conventional English learning. Data were collected through observation, language skills tests (including listening, speaking, and vocabulary skills), and interviews with teachers and parents. The results showed that the experimental group experienced significant improvements in English skills, especially in vocabulary mastery and speaking ability, compared to the control group. Children exposed to picture stories participated more actively in class discussions and showed greater interest in English learning. This study also identified challenges in implementing this method, such as the need for culturally relevant story selection and adequate training for teachers. Overall, the results of this study support the use of picture stories as an effective method to improve English language skills in early childhood and provide practical implications for the development of English language education curriculum at the kindergarten level.